Joint contact forces with changes in running stride length and midsole stiffness - Thomas, J. M.; Edwards, W. B.; Derrick, T. R. (Journal of Science in Sport and Exercise, 2020)
The purpose of this study was to determine if lower extremity joint loading was influenced by stride length or shoe midsole cushioning. Ten subjects completed 10 trials of overground running at an average speed of 4.43 m/s in each of three conditions: normal running, running with a stride length (SL) reduced by 10% of normal, and running with a cushioned midsole stiffness (i.e., mechanical impact reduction of 13.7-10.9 g). Reaction forces calculated from inverse dynamics were summed with muscle forces estimated from a musculoskeletal model using static optimization to obtain joint contact forces at the hip, knee and ankle joints. Peak components of the contact forces [axial, anterior-posterior, and medial-lateral (ML)] were examined using parametric statistics (a = 0.05). Reducing stride length resulted in significant decreases in absolute peak ankle contact forces in the axial direction (normal: - 14.5 ± 1.5 BW; reduced SL: - 14.0 ± 1.6 BW) and the ML direction (normal: 0.67 ± 0.23 BW; reduced SL: 0.61 ± 0.21 BW). Reducing stride length also reduced the peak absolute axial forces at the knee (normal: - 10.6 ± 1.3 BW; reduced SL: - 9.8 ± 1.2 BW) and the hip (normal: - 7.26 ± 2.24 BW; reduced SL: - 6.75 ± 2.10 BW). The cushioned shoe did not statistically reduce the peak absolute contact forces from the normal stride condition at any of the joints. Post hoc stress analysis suggested that the observed changes in anterior hip force would increase stress more than any of the other statistically significant results. Reductions in stride length appear to decrease some joint contact variables but cushioning in the heel region of the shoe does not.